Sox2 Cooperates with Inflammation-Mediated Stat3 Activation in the Malignant Transformation of Foregut Basal Progenitor Cells - Liu, Kuancan (2013)
Sox2 regulates the self-renewal of multiple types of stem cells. Recent studies suggest it also plays oncogenic roles in the formation of squamous carcinoma in several organs, including the esophagus where Sox2 is predominantly expressed in the basal progenitor cells of the stratified epithelium. Here, we use mouse genetic models to reveal a novel mechanism by which Sox2 cooperates with microenvironmental signals to malignantly transform epithelial progenitor cells. Conditional overexpression of Sox2 in basal cells expands the progenitor population in both the esophagus and forestomach. Significantly, carcinoma only develops in the forestomach where pathological progression correlates with inflammation and nuclear localization of Stat3 in progenitor cells. Importantly, co-overexpression of Sox2 and activated Stat3 (Stat3C) also transforms esophageal basal cells but not the differentiated suprabasal cells. These findings indicate basal stem/progenitor cells are the cells-of-origin of squamous carcinoma and that cooperation between Sox2 and microenvironment-activated Stat3 is required for Sox2-driven tumorigenesis.